2023
DOI: 10.2147/ijgm.s405977
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Mind-Regulation Acupuncture Therapy on Serum Ghrelin, Gastric Inhibitory Polypeptide, Leptin, and Insulin Levels in Breast Cancer Survivors with Cancer-Related Fatigue: A Randomized Controlled Trial

Abstract: Aim The aim of this research is to analyze the effects of mind-regulation acupuncture on serum ghrelin, gastric inhibitory polypeptide, leptin, and insulin levels, fatigue, quality of sleep, depression, and quality of life in survivors of breast cancer with cancer-related fatigue. Methods Total 136 breast cancer survivors with cancer-related fatigue were randomly allocated to the mind-regulation acupuncture group and the control group in a 1:1 ratio, with 68 cases in ea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 38 publications
0
2
0
Order By: Relevance
“…A minimum of six acupuncture sessions (e.g., weekly for 6 weeks, three times per week for 3 weeks), each lasting at least 20 minutes, has significant effects on CRF ( 43 ). Two studies ( 44 , 45 ) demonstrated that acupuncture can inhibit neuroinflammation and gut inflammation by regulating the gut microbiota-gut-brain axis, decrease serum ghrelin, leptin, and insulin levels, and improve the dysfunction of the HPA axis to improve CRF. However, as further studies are still needed to verify the effects of acupuncture on CRF, the European Society for Medical Oncology panel has not yet reached a consensus on the recommendation of acupuncture for reducing CRF.…”
Section: Discussionmentioning
confidence: 99%
“…A minimum of six acupuncture sessions (e.g., weekly for 6 weeks, three times per week for 3 weeks), each lasting at least 20 minutes, has significant effects on CRF ( 43 ). Two studies ( 44 , 45 ) demonstrated that acupuncture can inhibit neuroinflammation and gut inflammation by regulating the gut microbiota-gut-brain axis, decrease serum ghrelin, leptin, and insulin levels, and improve the dysfunction of the HPA axis to improve CRF. However, as further studies are still needed to verify the effects of acupuncture on CRF, the European Society for Medical Oncology panel has not yet reached a consensus on the recommendation of acupuncture for reducing CRF.…”
Section: Discussionmentioning
confidence: 99%
“…The mechanism by which AC treatment reduces fatigue may be closely related to the gut microbiota‐gut‐brain axis 65 . AC can reduce levels of gastric inhibitory peptide, leptin, and insulin in patients with breast cancer fatigue 66 . Previous studies have shown that AC can also alleviate insomnia through various mechanisms, including decreasing sympathetic activity, 131 inhibiting the activation of the hypothalamic‐pituitary‐adrenal axis, 132 increasing γ‐aminobutyric acid levels and receptors, 133 and increasing melatonin production and secretion 134 .…”
Section: Mechanisms Of Acupuncture In Cancer Therapymentioning
confidence: 99%